"A DERMATOGLYPHIC STUDY OF IRANAIAN MUSLIMS PART I: FINGER PATTERNS AND RIDGE-COUNTS " - M.Mehdipour; D.D.Farhud (Tehran University of Medical Sciences, 1978)
Finger Patterns and ridge-counts in a random sample of Iranian Muslims consisting of 100 males and 100 females are described. The most common finger patterns found were loops, having a frequency of 54.4% U.L., 3.4% R.L. in males and 51.2% U.L. and 4.8% R.L in females. The frequencies of arches and whorls in both sexes were 4% and 38.5% respectively. Bimanual and sex differences were indistinct. A Pattern type index of 11.85 and a pattern intensity index of 13.39 were found in both sexes combined. The mean total finger ridge-count observed is 166.54 in males and 160.93 in females. A significant sex difference of mean ridge-count was observed for digit numbers L3, L4, R2 and also for the total finger ridge-count with regard to bimanual difference for digit 2 in males and for digit 3 in females. The interpretation of the noted observations is discussed.